Highly Flexible and Broad-Range Mechanically Tunable All-Wood Hydrogels with Nanoscale Channels via the Hofmeister Effect for Human Motion Monitoring - Yan, Guihua; He, Shuaiming; Chen, Gaofeng; Ma, Sen; Zeng, Anqi; Chen, Binglin; Yang, Shuliang; Tang, Xing; Sun, Yong; Xu, Feng; Lin, Lu; Zeng, Xianhai (Nano-Micro Letters, 2022)
Wood-based hydrogel with a unique anisotropic structure is an attractive soft material, but the presence of rigid crystalline cellulose in natural wood makes the hydrogel less flexible. In this study, an all-wood hydrogel was constructed by cross-linking cellulose fibers, polyvinyl alcohol (PVA) chains, and lignin molecules through the Hofmeister effect. The all-wood hydrogel shows a high tensile strength of 36.5 MPa and a strain up to ~ 438% in the longitudinal direction, which is much higher than its tensile strength (~ 2.6 MPa) and strain (~ 198%) in the radial direction, respectively. The high mechanical strength of all-wood hydrogels is mainly attributed to the strong hydrogen bonding, physical entanglement, and van der Waals forces between lignin molecules, cellulose nanofibers, and PVA chains. Thanks to its excellent flexibility, good conductivity, and sensitivity, the all-wood hydrogel can accurately distinguish diverse macroscale or subtle human movements, including finger flexion, pulse, and swallowing behavior. In particular, when “An Qi” was called four times within 15 s, two variations of the pronunciation could be identified. With recyclable, biodegradable, and adjustable mechanical properties, the all-wood hydrogel is a multifunctional soft material with promising applications, such as human motion monitoring, tissue engineering, and robotics materials. Highlights: 1 An all-wood hydrogel was synthesized via a simply Hofmeister effect without the use of any chemical cross-linking agent. 2 The all-wood hydrogel shows a high tensile strength of 36.5 MPa, a strain up to ~ 438%, and good conductivity, and can accurately distinguish diverse large or subtle human movements. 3 The all-wood hydrogel has good recyclable, biodegradable, and adjustable mechanical properties.